Effects of the Histone Deacetylase Inhibitor ITF2357 in Autoinflammatory Syndromes - Bodar, Evelien J (ScholarOne, 2011)
We explored the effects of the oral histone deacetylase (HDAC) inhibitor ITF2357 in patients with autoinflammatory syndrome. In this prospective open-label pilot study, eight patients were enrolled; one patient with tumor necrosis factor receptor–associated periodic syndrome (TRAPS), three patients with hyper-IgD and periodic fever syndrome (HIDS) and four patients with Schnitzler syndrome were closely followed during 90 d of ITF2357 treatment. Three patients with Schnitzler syndrome and one TRAPS patient experienced a partial remission. In four patients, there was no effect. In HIDS patients, there was a tendency toward a higher attack frequency and increasing attack severity. In two patients (one TRAPS and one HIDS), we observed a decrease of acute-phase response without signs of clinical improvement. One patient with Schnitzler syndrome showed a partial response despite an ongoing acute-phase response. In conclusion, ITF2357 monotherapy was able to induce partial response only in patients with Schnitzler syndrome and no response in patients with HIDS.